“Separation, but not Division”: A Southern Italian Perspective on “Lived Conspirituality” - Parmigiani, Giovanna (Anthropologica)

(untitled) (University of Victoria, 2023)
Conspirituality—that is, the connection between conspiracy theories and spirituality—has recently gained popularity in academic and non-academic circles. Often associated with populist and irrational beliefs, it has been linked to right-wing politics, faulty thinking, and disruptive and potentially violent behaviour (Greenwood 2022; Russell 2022). While these connections have been proven to be true in some cases, in this paper, rooted in my long-standing ethnographic research, I offer a contribution that illuminates other aspects of conspirituality—in line with recent attempts to honour the complexity and internal variability of the phenomenon (for example, Greenwood 2022; Ong 2021). In particular, differently from the overwhelming majority of current approaches in the study of conspirituality, I propose to frame the study of conspirituality not only by focusing on ideas and beliefs, but in conversation with the study of “lived religion” (see, for example, Ammerman 2021; Hall 2001; McGuire 2008) in a way that distinguishes the actual experience of persons from normative beliefs and practices. Similarly to what the study of “lived religion” does to the study of religion, I claim that the study of “lived conspirituality” could offer insights into the phenomenon of conspiracism, today (Ong 2020). By analyzing discourses and practices of conspiritualists that I observed on the field, I will challenge mainstream interpretations of the role of the individual and of marginality in New Age conspirituality.